(3eNJUQ aj Yde GdeaJhM ef Yde GdMSGHs - (3GHf adhS , CHj GdWGgQ TeS GdOjf ESeGYjd Hf EHQGgje Hf ZGRj GdeGQOjfj GdfejQj, GHf adhS,J (B650 (3g` s ((3CMeO Hf GHQGgje GdSWMi s)
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ GdeGQOjfi gPG eNJUQ ai Yde GdeaJhM ef Yde GdMSGH GdHGH GdChd ai PcQ GSeGA hYbhO eQGJH OGFQI ai Yde GdMSGH s
(3BNQgG (B:s
(3gPG LOhd GdNeSI hCQHYjf eSFdI GdPi dGHO ddeHJOF ef QjGVI NGWQg ajgG dEYGfJgG EjGg Ydi eG ahbgG hGddg GYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdGeHQhRjGfG s
(3JHUQI GdJQGLe(Bs
Keywords: (3Gdadcs